Peningkatan Aktivitas dan Hasil Belajar IPA pada Siswa SMP Melalui Model Discovery Learning - Eko Purwanti (Jurnal Didaktika Pendidikan Dasar, 2022)
Conventional learning makes students quickly bored and not interested in taking part in learning optimally. This can lead to low student activity and participation in learning. The problem is how the discovery learning model can activate students and improve their learning outcomes? The purpose of this study was to (1) increase learning activities in magnetic material through learning with the discovery learning model in class IXE students of SMP N 2 Pringapus in the 2019/2020 academic year; (2) increase learning outcomes in magnetic materials through discovery learning models in class IXE students of SMP N 2 Pringapus in the 2019/2020 academic year.The results showed that learning with the discovery learning model can increase student learning activities through participation in learning by 85.83%, an increase in learning activities by 40.83%, and can improve student learning outcomes in class IXE in the academic year of SMP N 2 Pringapus in 2019/2020. amounted to 24.59%.